Varicella-Zoster Virus Open Reading Frame 66 Protein Kinase and Its Relationship to Alphaherpesvirus US3 Kinases - Erazo, Angela (2010)
The varicella-zoster virus (VZV) open reading frame (ORF) 66 encodes a basophilic kinase orthologous to the US3 protein kinases found in all alphaherpesviruses. This review summarizes current information on the ORF66 kinase, and outlines apparent differences from other US3 kinases, as well as some of the conserved functions. One critical difference is the VZV ORF66 kinase targeting of the major regulatory VZV IE62 protein to control its nuclear import and assembly into the VZV virion, which is so far unprecedented in the alphaherpesviruses. However, ORF66 targets some cellular targets which are also targeted by US3 kinases of other herpesviruses, including the histone deacetylase-1 and 2 proteins, pathways that lead to changes in actin dynamics, and the targeting of substrates of protein kinase A, including the nuclear matrix protein matrin 3.